VK-æraens departementschefer – troldmændene fra Oz - Nielsen, Peter Heyn (Politik, 2014)
Denmark has upheld a pure merit civil service, but an ever increasing workload is burdening the ministers, forcing the permanent secretaries to take part in a large part of the political work, which ideally would be assigned only to the ministers. is article explores who the persons were, that held o ce as permanent secretaries in Denmark during the Liberal-Conservative governments from 2001 to 2011 in a historical perspective. Data shows that these permanent secretaries on several criteria di er signi cantly from what has been the Danish tradition. e criteria on which the greatest changes have taken place are education, age of leaving o ce, terms in o ce and former careers.